The Use of Skimming and Scanning in Reading Comprehension at SMA Gajah Mada 3 Palembang - Novasyari, Ressy (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
Abstract : In our daily lives, in homes, in school and on the streets, to read is necessary for livelihood and survival. It means that, we learn something by reading or we can say that reading is the central to the learning process to know something. Reading is a key towards civilizations progress. Since the invention of alphabet as a means of written communications, reading ability has becomes essential for character building and national development. Nowadays, many children are lazy to read. They interested in watching TV, listening music, playing games and hanging out with their friends. There are some factors that caused the student reading ability poor. The factors are classified into two internal and external factors. The internal factors come from studentt themselves such as motivation, and knowledge. The external factor come from teacher, school facilities parents and the condition that influences the student in learning English. A teacher can use several techniques for their teaching in reading comprehension. The techniques are skimming and scanning. Keywords : Skimming, Scanning and Reading Comprehension